Temperature dependent anomalous fluctuations in water: shift of ≈1 kbar between experiment and classical force field simulations. (17th November 2019) - Pathak, Harshad; Späh, Alexander; Amann-Winkel, Katrin; Perakis, Fivos; Kim, Kyung Kyung Hwan; Nilsson, Anders
Abstract : Here we report on the temperature dependence of the anomalous behaviour of water in terms of (i) its growth in tetrahedral structures, (ii) instantaneous spatial correlations from small angle x-ray scattering (SAXS) data, (iii) estimates of thermodynamic response functions of isothermal compressibility and (iv) thermal expansion coefficient. Water's thermal expansion coefficient is estimated for the first time at supercooled conditions from liquid water's structure factor. We used previously published data from classical force-fields of TIP4P/2005 and iAMOEBA to compare experimental data with molecular dynamics simulations and observe that these force-fields underestimate water's anomalous behaviour but perform better upon increasing pressure. We demonstrate that the molecular dynamics simulations can describe better the temperature dependent anomalous behaviour of ambient pressure water if simulated at 1 kbar. The deviation in anomalous fluctuations in the simulations is not restricted to ≈228 K but extends all the way to ambient temperatures. GRAPHICAL ABSTRACT: